To B or Not to B: Understanding B Cell Responses in the Development of Malaria Infection - Silveira, Eduardo L. V.; Dominguez, Mariana R.; Soares, Irene S. (Frontiers in Immunology, 2018)
Malaria is a widespread disease caused mainly by the Plasmodium falciparum (Pf) and Plasmodium vivax (Pv) protozoan parasites. Depending on the parasite responsible for the infection, high morbidity and mortality can be triggered. To escape the host immune responses, Plasmodium parasites disturb the functionality of B cell subsets among other cell types. However, some antibodies elicited during a malaria infection have the potential to block pathogen invasion and dissemination into the host. Thus, the question remains, why is protection not developed and maintained after the primary parasite exposure? In this review, we discuss different aspects of B cell responses against Plasmodium antigens during malaria infection. Since most studies have focused on the quantification of serum antibody titers, those B cell responses have not been fully characterized. However, to secrete antibodies, a complex cellular response is set up, including not only the activation and differentiation of B cells into antibody-secreting cells, but also the participation of other cell subsets in the germinal center reactions. Therefore, a better understanding of how B cell subsets are stimulated during malaria infection will provide essential insights toward the design of potent interventions.